Antimicrobial resistance and genomic analysis of Vibrio parahaemolyticus isolates from foodborne outbreaks, Huzhou, China, 2019–2023 - Yan, Wei; Ji, Lei; Dong, Fenfen; Chen, Liping; Yuan, Rui; Zhang, Peng (Frontiers in Microbiology, 2024)
Objective: The purpose of this study was to investigate the epidemiological and genomic characteristics of Vibrio parahaemolyticus(V. parahaemolyticus) isolates from outbreaks in Huzhou, China. Methods: To analyze the epidemiological data on V. parahaemolyticus outbreaks reported in Huzhou from 2019 to 2023. A total of 70 V. parahaemolyticus outbreaks isolates were collected. The antibiotic resistance, serotypes, molecular typing andgenomic characteristics of these isolates were analyzed. Results: Most outbreaks of V. parahaemolyticus infection occured in the summer, and the majority of outbreaks occur in restaurants and rural banquet. High resistance rates were observed for AMP (24.29%), followed by TET (15.71%) and SXT (15.71%). The newly emerged serotype O10:K4 became dominant from 2021 to 2023, with most isolates belonging to ST3. The resistance gene blaCARB was frequently detected among these isolates.The Pulsed field gel electrophoresis (PFGE) and whole-genome single-nucleotide polymorphisms (wgSNPs) effectively differentiated the nine outbreaks. Conclusion: The newly emerged serotype O10:K4 became dominant from 2021 to the present, and most of isolates were ST3. PFGE and WGS technologies provided reliable methods for typing and identification of V. parahaemolyticus for outbreaks. Key words: Vibrio parahaemolyticus, foodborne disease, outbreak, PFGE, WGS